Mid Pleistocene foraminiferal mass extinction coupled with phytoplankton evolution - Kender, Sev; McClymont, Erin L.; Elmore, Aurora C.; Emanuele, Dario; Leng, Melanie J.; Elderfield, Henry (Nature Publishing Group, 2016)
Understanding the interaction between climate and biotic evolution is crucial for deciphering the sensitivity of life. An enigmatic mass extinction occurred in the deep oceans during the Mid Pleistocene, with a loss of over 100 species (20%) of sea floor calcareous foraminifera. An evolutionarily conservative group, benthic foraminifera often comprise 450% of eukaryotebiomass on the deep-ocean floor. Here we test extinction hypotheses (temperature corrosiveness and productivity) in the Tasman Sea, using geochemistry and micropalaeontology and find evidence from several globally distributed sites that the extinction was caused by a change in phytoplankton food source. Coccolithophore evolution may have enhanced the seasonal ‘bloom’ nature of primary productivity and fundamentally shifted it towards a more intra-annually variable state at B0.8 Ma. Our results highlight intra-annual variability as a potential new consideration for Mid Pleistocene global biogeochemical climate models, and imply that deep-sea biota may be sensitive to future changes in productivity.